Photoemission spectroscopy study of structural defects in molybdenum disulfide (MoS2) grown by chemical vapor deposition (CVD) - Syari’ati, Ali; Kumar, Sumit; Zahid, Amara; El Yumin, Abdurrahman Ali; Ye, Jianting; Rudolf, Petra (Chemical communications, 2019)
The fingerprint of structural defects in CVD grown MoS2 was revealed by means of X-ray Photoelectron Spectroscopy (XPS). These defects can be partially healed by grafting thiol-functionalized molecules. The functionalization does not alter the semiconducting properties of MoS2 as confirmed by the photoluminescence spectra.
Im Titel ist "2" bei MoS2 tiefgestellt
Gesehen am 11.03.2021